Study on Load-Participated Demand Response Model Based on Load Aggregator - Pei, Zixia; Ma, Yunlong; Wu, Mengyun; Yang, Jianlan (Frontiers in Energy Research, 2021)
The reform of electricity market, along with the gradual opening of the electricity sales side as well as the increase of the proportion of residential electricity consumption, the user load of demand side has become an essential resource for demand response (DR). To efficiently utilize the residential load resources, new market participants such as load aggregator (LA) have emerged. Firstly, the basic concept of LA is introduced in this paper; the origin and definition of LA is studied; the classification of aggregated resources and the current situation of LA operation in some countries are presented. Then, the article analyzes the market operation mode of LA and the uncertainty in LA the operation in detail, including the LA service on the user side, the transaction mode and hierarchical structure associated with operation, the uncertainty classification analysis and associated strategies to address the problem. The LA load integration method and the scheduling control strategy are discussed. Finally, suggestions and ideas on the future research direction are proposed.